Steel slag aggregate capable of improving stability of cement steel slag concrete as well as preparation method and application of steel slag aggregate
By performing the coating modification treatment of the steel slag aggregates with regenerated micro powder and ground polymer mixture, the problem of poor stability caused by uneven volume expansion in the concrete is solved, and the effect of improving the stability and mechanical properties of concrete is achieved. At the same time, it reduces production costs.
Patent Information
- Application Number
- CN202411580785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
When used in concrete, steel slag is poor in stability due to uneven volume expansion. The existing treatment methods have problems such as high time cost, high economic cost and poor treatment effect.
The steel slag aggregate is coated and modified by the polymer mixture in a coordinated manner to form a dense three-dimensional interpenetrating network structure, reducing the expansion force conduction during steel slag expansion, and inhibiting the contact between the steel slag and water.
It improves the stability of steel slag concrete, improves the mechanical properties of concrete, reduces production costs, and improves the utilization rate of steel slag.
Smart Images

Figure HDA0005123041540000011 
Figure HDA0005123041540000012 
Figure HDA0005123041540000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid resource utilization, and specifically relates to a steel slag aggregate capable of improving the stability of cement steel slag concrete, and a preparation method and application thereof. Background Art
[0002] Steel slag is a waste residue produced during the steelmaking process. Due to its poor stability, steel slag is difficult to be widely used in concrete, especially when steel slag is used as an aggregate in concrete, the stability problem of concrete becomes more and more significant, making it difficult to use steel slag on a large scale in the field of concrete. At present, how to improve the stability of steel slag and utilize it as a resource has become an urgent problem to be solved.
[0003] The main reason for the volume expansion of steel slag is that the steel slag particles contain some f-CaO and f-MgO, which can slowly react with water to generate Ca(OH)2 and Mg(OH)2, resulting in volume expansion. There are several main solutions to the volume expansion of steel slag at home and abroad: Eliminate f-CaO in steel slag. Most domestic studies are to treat steel slag with carbonation and aging to dissolve f-CaO in steel slag. There are also studies that use chemical activators to treat steel slag to reduce the f-CaO content in steel slag; secondly, modify the surface of steel slag by applying an organic protective layer, such as epoxy resin, silicone resin, etc. to prevent steel slag from contacting water to inhibit the hydration of f-CaO in steel slag. The above methods can improve the stability of steel slag to a certain extent, but on the other hand, the above methods have the problems of long time cost and high economic cost for the treatment of steel slag. For example, the aging treatment takes a long time and the effect is not significant, and the carbonation treatment has a high economic cost; the use of surface modifiers and chemical activators has a high economic cost, the process is more complicated and the treatment effect is not good. When steel slag aggregate is used in concrete, it will also cause volume stability problems. The above methods have increased the production cost to a certain extent and limited the utilization rate of steel slag. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a steel slag aggregate and a preparation method and application thereof for improving the stability of cement steel slag concrete in view of the deficiencies in the prior art. The steel slag aggregate provided by the present invention can solve the problem of uneven expansion of steel slag aggregate, improve the stability of steel slag concrete, and increase the utilization rate of steel slag.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete comprises the following steps:
[0007] (1) using recycled micro powder to coat steel slag to form a coating;
[0008] (2) uniformly mixing an alkali activator, regenerated micropowder and a siliceous aluminum raw material to obtain a geopolymer mixture; wherein the alkali activator is a mixture of carbide slag, sucrose, sodium sulfate and water; and the siliceous aluminum raw material is one of mineral powder, fly ash and metakaolin;
[0009] (3) The obtained geopolymer mixture is used to coat the obtained coated body, and after standing and drying, a steel slag aggregate having improved stability of cement steel slag concrete is obtained.
[0010] In the above scheme, the mass ratio of the regenerated micropowder in step (1), the steel slag and the geopolymer mixture in step (2) is (10-20): (45-80): (10-20).
[0011] In the above scheme, the composition of the geopolymer mixture is counted by mass as follows: 65-110 parts of alkali activator, 30-40 parts of silicon-aluminum raw material, and 45-55 parts of regenerated micropowder.
[0012] In the above scheme, the composition of the alkaline activator is counted by mass as follows: 10-20 parts of carbide slag, 20-30 parts of sucrose, 5-10 parts of sodium sulfate, and 30-50 parts of water.
[0013] In the above scheme, the particle size of the steel slag is 4.75-26.5 mm.
[0014] In the above scheme, the regenerated micro powder includes one of brick-concrete regenerated micro powder, regenerated brick powder and regenerated concrete powder; the brick-concrete regenerated micro powder is a mixture of regenerated brick powder and regenerated concrete powder.
[0015] In the above solution, the particle size of the regenerated micro powder is not greater than 80 μm.
[0016] In the above scheme, the particle size of the carbide slag is 10-100 μm.
[0017] In the above scheme, the particle size of the silicon-aluminum raw material is 10-100 μm.
[0018] In the above scheme, the mineral powder is a by-product of iron smelting, and the specification is S95 mineral powder.
[0019] In the above scheme, the coating treatment is specifically: mixing and stirring for 15-40 minutes, and then standing for 1-24 hours.
[0020] The present invention also claims protection for the steel slag aggregate prepared by the above preparation method, wherein the particle size of the steel slag aggregate is 9.5-31.5 mm.
[0021] The present invention also claims to protect the concrete prepared by the above-mentioned steel slag aggregate, in which the steel slag aggregate replaces a part of the aggregate in equal amount, and the replacement amount is 5%-40% of the mass of the aggregate.
[0022] The f-CaO in steel slag is unevenly distributed, and reacts with water to generate Ca(OH)2, resulting in volume expansion. When steel slag is added to concrete as aggregate, a large number of cracks will be generated in the interface area inside the concrete and the structural integrity will be lost, which will then manifest as poor concrete volume stability. Therefore, the concrete cracking time and severity caused by the poor volume stability of steel slag aggregate are uncertain and difficult to predict. To solve this problem, the present invention uses recycled micropowder to synergize with a geopolymer mixture to coat and modify the steel slag aggregate. The formed coating has a dense three-dimensional interpenetrating network structure that can strengthen the surface interface of the steel slag and reduce the conduction of the expansion force when the steel slag expands. The coating also has a certain water-insulating property. At the same time, the recycled micropowder in the coating also has strong water absorption. The recycled micropowder is hydrated to form a dense polymer structure, which further inhibits the steel slag from contacting with water. At the same time, the present invention uses carbide slag alkali to activate siliceous and aluminous raw materials to prepare geopolymers, wherein sucrose and sodium sulfate are added to enhance the alkalinity of the alkali activator, and the introduction of sodium silicate can form calcium aluminate at an early stage to improve the overall strength. Through this method, a coating layer is formed on the surface of steel slag to inhibit the uneven expansion of steel slag. At the same time, the geopolymer mixture, recycled micropowder and steel slag have good bonding properties, which can improve the aggregate interface strength, improve the stability of concrete, and improve its mechanical properties.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The steel slag aggregate provided by the present invention can solve the problem of uneven expansion of steel slag aggregate, improve the stability of steel slag concrete, and enhance the mechanical properties of the concrete steel slag region interface.
[0025] (2) The preparation method provided by the present invention has a simple process, reduces production costs, and improves the utilization rate of steel slag. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a picture of the steel slag aggregate prepared in Example 1 of the present invention that improves the stability of cement steel slag concrete.
[0027] Figure 2 This is a picture of the crushed steel slag aggregate prepared in Example 1 of the present invention for improving the stability of cement steel slag concrete.
[0028] Figure 3 This is a picture of concrete prepared with steel slag aggregate having improved stability of cement steel slag concrete prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0030] The particle size of the carbide slag used in the embodiments of the present invention and the comparative examples is 10-100 μm; the particle size of the mineral powder is 10-100 μm, and the mineral powder specification is S95.
[0031] Example 1
[0032] A method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete comprises the following steps:
[0033] (1) Using brick-concrete recycled micropowder with a particle size not higher than 80 μm (recycled brick powder and recycled concrete powder are mixed in a mass ratio of 3:2) to vibrate and coat steel slag with a particle size range of 4.75-16 mm to form a coating; the weight percentage of the brick-concrete recycled micropowder in the coating is 20%, and the weight percentage of the steel slag is 80%.
[0034] (2) 5 parts by weight of carbide slag, 10 parts by weight of sucrose, 3 parts by weight of sodium silicate and 15 parts by weight of water are prepared to form an alkali activator, and 25 parts by weight of brick-concrete recycled micropowder and 20 parts by weight of mineral powder are added and mixed evenly to obtain a geopolymer mixture.
[0035] (3) Add 300 parts of the coating to the obtained geopolymer mixture and stir and mix for 30 minutes; take it out from the mixer and let it stand for 24 hours, then dry and naturally cure to obtain steel slag aggregate with improved stability of cement steel slag concrete. See the relevant pictures. Figure 1 , Figure 2 , wherein the obtained steel slag aggregate particle size is 9.5-31.5mm.
[0036] The steel slag aggregate with a particle size of 4.75-16 mm obtained by the above method was added at a rate of 40% to replace the same grade crushed stone to prepare C30 concrete. A 100mm×100mm×100mm mold was used. After 1 day of molding, the steel slag concrete test block was demoulded to obtain the relevant pictures. Figure 3 .
[0037] Stability test method: The above concrete test blocks are subjected to autoclave test with a treatment time of 3 hours at a stable temperature of 216°C for 3 hours. The surface of the test piece after autoclave is observed for protrusions, number of detached cracks, etc. If the test piece is intact, the strength loss rate of the test piece after autoclave is tested.
[0038] Mechanical properties test method: The compressive strength test of the above concrete specimens was carried out after curing for 28 days.
[0039] The 28d compressive strength of the concrete prepared in this embodiment is 44.18 MPa, and the autoclave strength loss rate is 14.03%. After autoclaving, there are no cracks on the surface of the specimen, but there are 2 defects.
[0040] Example 2
[0041] This embodiment is basically the same as the embodiment 1, except that the recycled brick powder is used to replace the brick-concrete recycled micro powder.
[0042] The 28d compressive strength of the concrete prepared in this embodiment is 42.56 MPa, and the autoclave strength loss rate is 18.50%. After autoclaving, there are no cracks on the surface of the specimen, but 4 defects appear.
[0043] Example 3
[0044] This embodiment is basically the same as the embodiment 1, except that the recycled concrete powder is used to replace the brick-concrete recycled micro powder.
[0045] The 28d compressive strength of the concrete prepared in this embodiment is 42.24 MPa, and the autoclave strength loss rate is 21.24%. After autoclaving, there are no cracks on the surface of the specimen, but 4 defects appear.
[0046] Comparative Example 1
[0047] This comparative example is basically the same as Example 1, except that the brick-concrete recycled fine powder in step (1) is not used to coat the steel slag, and the geopolymer mixture in step (2) does not contain brick-concrete recycled fine powder.
[0048] The 28d compressive strength of the concrete prepared in this comparative example is 37.74Mpa, and the autoclave strength loss rate is 27.40%. After autoclaving, there are no cracks on the surface of the test piece, but 8 defects appear.
[0049] Comparative Example 2
[0050] This comparative example is basically the same as Example 1, except that the brick-concrete recycled fine powder in step (1) is not used to coat the steel slag, and the geopolymer mixture in step (2) contains brick-concrete recycled fine powder.
[0051] The 28d compressive strength of the concrete prepared in this comparative example is 39.19 MPa, and the autoclave strength loss rate is 25.63%. After autoclaving, there are no cracks on the surface of the test piece, but 6 defects appear.
[0052] Comparative Example 3
[0053] This comparative example is basically the same as Example 1, except that the geopolymer mixture in step (2) is not used to coat the steel slag, and cement slurry of equal mass is used instead of geopolymer to coat the steel slag aggregate.
[0054] The 28d compressive strength of the concrete prepared in this comparative example is 41.20 MPa, and the autoclave strength loss rate is 55.56%. After autoclaving, cracks appear on the surface of the test piece, and 10 defects appear.
[0055] Comparative Example 4
[0056] This comparative example is basically the same as Example 1, except that the coating of the steel slag with the brick-concrete recycled micropowder in step (1) is not performed, and the coating of the steel slag with the geopolymer mixture in step (2) is not performed.
[0057] The 28d compressive strength of the concrete prepared in this comparative example is 37.25 MPa, and the autoclave strength loss rate is 100%. After autoclaving, cracks appear on the surface of the specimen and the specimen collapses.
[0058] It can be seen from the experimental results of the above embodiments and comparative examples that the steel slag aggregate prepared by the method can not only improve the problem of poor stability of concrete, but also improve the mechanical properties of concrete to a certain extent. Compared with traditional cement steel slag concrete, it has the characteristics of high stability and excellent mechanical properties. It has broad application prospects in the field of building materials and improves the utilization rate of steel slag.
[0059] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete, characterized in that: The following steps are involved: (1) using recycled micro powder to coat steel slag to form a coating; (2) uniformly mixing an alkali activator, regenerated micropowder and a siliceous aluminum raw material to obtain a geopolymer mixture; wherein the alkali activator is a mixture of carbide slag, sucrose, sodium sulfate and water; and the siliceous aluminum raw material is one of mineral powder, fly ash and metakaolin; (3) The obtained geopolymer mixture is used to coat the obtained coated body, and after standing and drying, a steel slag aggregate having improved stability of cement steel slag concrete is obtained.
2. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The mass ratio of the regenerated micropowder in step (1), the steel slag and the geopolymer mixture in step (2) is (10-20): (45-80): (10-20).
3. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The composition of the geopolymer mixture is counted by mass as follows: 65-110 parts of alkali activator, 30-40 parts of silicon-aluminum raw material, and 45-55 parts of regenerated micro powder.
4. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The composition of the alkaline activator is counted by mass: 10-20 parts of carbide slag, 20-30 parts of sucrose, 5-10 parts of sodium sulfate, and 30-50 parts of water.
5. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The particle size of the steel slag is 4.75-26.5 mm.
6. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The regenerated micro powder includes one of brick-concrete regenerated micro powder, regenerated brick powder and regenerated concrete powder.
7. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The particle size of the regenerated micro powder is not greater than 80 μm; the particle size of the carbide slag is 10-100 μm; and the particle size of the silicon-aluminum raw material is 10-100 μm.
8. The method for preparing steel slag aggregate capable of improving the stability of cement steel slag concrete according to claim 1, characterized in that: The coating treatment is specifically as follows: mixing and stirring for 15-40 minutes, and then standing for 1-24 hours.
9. The steel slag aggregate prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The particle size of the steel slag aggregate is 9.5-31.5 mm.
10. A concrete prepared using the steel slag aggregate according to claim 9, characterized in that: In the concrete, the steel slag aggregate replaces a part of the aggregate in equal amount, and the replacement amount is 5%-40% of the mass of the aggregate.
Citation Information
Cited By
Method for densification regulation and full utilization of steel slag
CN120505464A